Factors hampering the implementation of gender equality in the workplace - Debbie Jansen; Shikha Vyas-Doorgapersad (Insights into Regional Development)
The level of gender equality is different in every country and every culture, and, therefore, the history and conceptual framework for each country and culture are different. The article examines the causes of the inequality experienced by women in a general context, drawn from a qualitative approach that utilises a desktop analysis of secondary sources. Based on the advantages of the Gender and Development (GAD) approach explored in the study, such as its focus on women's needs, gender relations, and the state's role, it was determined that the GAD theory provided the most suitable framework for this study. The findings explore that there are varied causes of gender inequality divided into ideological factors, social system factors, economic factors, and political factors. Added to this are the causes of gender inequality in the workplace, which refers to human resource practices, job segregation, pay gap, lack of commitment, glass ceiling and escalator, and the lack of female role models. The study suggests that gender equality can bring employee satisfaction to the workplace and positive economic growth to society. The importance thereof in the achievement of the sustainable development goals (SDGs), especially sustainable development goal number 5 (SDG5) (gender equality and women empowerment), can thus not be disputed.